Preliminary Study on assessing factors influencing learning problem among students of PROTIM class in Kota Kinabalu - Khin Win Thawdar; Maher F. Sefein; P.Muthusamy; N. Kumaraswaml; Amran Ahmed (Universiti Malaysia Sabah, 2010)
Learning problems can be due to so many factors that may have impact on the child. PROTIM is a remedial programme designed to ensure students of year 4, 5 and 6 to acquire basic literacy (Bahasa Malaysia) and numeracy skills. Student populations in primary school consist of students having different level of intelligence and vary accordingly in their level of performance in reading, writing and arithmetic. We chose 7 primary schools from Kota Kinabalu area to find out factors influencing learning problems in students of PROTIM class. Information regarding parents back-ground and student's development history were collected by questionnaires, written in Malaysian language, were distributed before medical examination were carried out on the students participated in the study. We expected to find a lot of factors that can influence the . learning problems in students of PROTIM class in Kota Kinabalu. Only hypertension in pregnancy, neonatal jaundice treatment and parent's education were correlated with the intellectual of students. 22.7 % of students of PROTIM gave history of hearing loss. Out of those, 64,5% had normal, 16.1% and 19.4% had one-sided and both-sided abnormal tympangram respectively. But there were no significant correlation with abnormal tympanogram and learning problem, Further research covering a wider area is needed to look for factors relating to problems of learning in these children